Role of ethical beliefs and attitudes of dental students in providing care for HIV/AIDS patients - Khan, S.A.; Liew, M.L.; Omar, H. (Elsevier, 2017)
Introduction Dental care has remained as an unmet need for people living with HIV/AIDS (PLWHAs). Dental students are considered as future healthcare workforce and having beliefs which are discriminating may have negative attitudes towards providing care to these individuals (Azodo et al., 2010). The study aimed to assess the ethical beliefs and attitudes of dental students towards PLWHAs for providing care. Methods It is a descriptive correlational and cross sectional study. Nine public and private dental schools in Malaysia participated in the study. Data was collected using a validated self-administered questionnaire. Results A total of 481 dental students participated in this study, yielding response rate of 78%. Majority of the participants (74%) believed that patients’ HIV status should be disclosed to patients’ sexual partner without permission. Approximately 60% of the participants reported that rooms/beds of HIV patients should be clearly marked. Regarding patient disease status 28% of the students reported that it is appropriate to test a patient for HIV/AIDS without patient's permission. Only Fifty five percent of the students expressed the willingness to treat HIV patients and 49% reported to held fear of getting infected while treating patients with HIV/AIDS. Sixty four percent of the participants reported to be more comfortable giving care to non-HIV patients than HIV-positive patients. Conclusion Dental students’ ethical beliefs about HIV/AIDS were not consistent with the ethical principles as stated in the code of ethics and they held negative attitudes towards PLWHAs. Ethical beliefs were found to be a determinant that may influence future attitudes of these students towards individuals with HIV/AIDS when providing care.